Port of shadows - Cook, Glen (Cook, Glen. Chronicle of the Black Company., 2018)
The soldiers of the Black Company don<U+2019>t ask questions, they get paid. But being “The Lady<U+2019>s favored” is attracting the wrong kind of attention and has put a target on their backs--and the Company<U+2019>s historian, Croaker, has the biggest target of all. The one person who was taken into The Lady<U+2019>s Tower and returned unchanged has earned the special interest of the court of sorcerers known as The Ten Who Were Taken. Now, he and the company are being asked to seek the aid of their newest member, Mischievous Rain, to break a rebel army. However, Croaker doesn<U+2019>t trust any of the Taken, especially not ones that look so much like The Lady and her sister<U+2026>